Dendritic calcium transients evoked by single back-propagating action potentials in rat neocortical pyramidal neurons. - Markram, H (1995)
1. Dendrites of rat neocortical layer V pyramidal neurons were loaded with the Ca2+ indicator dye Calcium Green-1 (CG-1) or fluo-3, and the mechanisms which govern action potential (AP)-evoked transient changes in dendritic cytosolic Ca2+ concentration ([Ca2+]i) were examined. APs were initiated either by synaptic stimulation or by depolarizing the soma or dendrite by current injection, and changes in fluorescence of the indicator dye were measured in the proximal 170 microns of the apical dendrite. 2. Simultaneous two-pipette recordings of APs from the soma and apical dendrite, and dendritic fluorescence imaging indicated that a single AP propagating from the soma into the apical dendrite evokes a rapid transient increase in fluorescence indicating a transient increase in [Ca2+]i. At 35-37 degrees C the decay time constant of the fluorescence transient following an AP was around 80 ms. 3. Voltage-activated Ca2+ channels (VACCs) of several subtypes mediated the AP-evoked fluorescence transient in the proximal (100-170 microns) apical dendrite. The AP-evoked fluorescence transient resulted from Ca2+ entry through L-type (nifedipine sensitive; 25%), N-type (omega-conotoxin GVIA sensitive; 28%) and P-type (omega-agatoxin IVA sensitive; 10%) Ca2+ channels and through Ca2+ channels (R-type) not sensitive to L-, N- and P-type Ca2+ channel blockers (cadmium ion sensitive; 37%). 4. The decay time course of the dendritic fluorescence transient was prolonged by the blockers of endoplasmic reticulum (ER) Ca(2+)-ATPase, cyclopiazonic acid and thapsigargin, suggesting that uptake of Ca2+ into the ER in dendrites governs clearance of dendritic Ca2+. 5. The decay time course of the fluorescence transient was slightly prolonged by benzamil, a blocker of plasma membrane Na(+)-Ca2+ exchange and by calmidazolium, a blocker of the calmodulin-dependent plasma membrane Ca(2+)-ATPase, suggesting that these pathways are less important for dendrite Ca2+ clearance following a single AP. Neither the mitochondrial uncoupler carbonyl cyanide p-(trifluoromethoxy)phenylhydrazone (FCCP) nor the blocker of Ca2+ uptake into mitochondria, Ruthenium Red, had any measurable effect on the decay time course of the fluorescence transient. 6. Dendritic fluorescence transients measured during trains of dendritic APs began to summate at impulse frequencies of 5 APs s-1. At higher frequencies APs caused a concerted and maintained elevation of dendritic fluorescence during the train.(ABSTRACT TRUNCATED AT 400 WORDS)